REGRESSIVE MODELS OF COMPUTED TOMOGRAPHY PARAMETERS OF LIQUOR RESTRAIN STRUCTURES OF THE BRAIN IN HEALTHY GIRLS - Moskovko, S.P.; Gunas, I.V.; Shevchuk, Yu.G. (World of Medicine and Biology, 2014)
The aim of this research was a construction of regressive models of normative computed tomography parameters of liquor restrain structures of the brain for the healthy municipal girls of Podolie with the mesocephal form of skull depending on the features of structure and sizes of body. For the practically healthy girls mesocephals more than in 85 % cases the built models of normative individual computed tomography parameters of liquor restrain structures of the brain, that have exactness of description of regressive dependence from 54,3 to 82,8 %. Most often to the built models entered: encompassing sizes of body (29,7 %), cephalometric sizes (19,5 %), diameters of body(15,3 %) and thickness of leather-fatty folds (12,7 %).
Keywords: regressive models; computed tomography; liquor restrain structures of the brain; healthy girls mesocephals; anthropometry